Происхождение удмуртского народа: [монография] / М. Г. Атаманов-Эграпи - Атаманов-Эграпи Михаил Гаврилович (Удмуртия, 2010)
Экземпляры: ЦБ (20130506) / Инвентарный номер: 44426 / Цена: 150.00 / Авт.знак: А 92 / ГРНТИ: 03 / ББК: 63.5(2Рос.Удм)